Grape-seed extract (oligomeric proanthocyanidin) or N-acetylcysteine antioxidant supplementation several days before and after an acute bout of plyometric exercise - Delport, Chris J. (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.